HUBUNGAN PARAMETER OSEANOGRAFI PERAIRAN TERHADAP POLA MUSIM IKAN PELAGIS DI PERAIRAN PALABUHANRATU - Pratama, Gilar Budi; Nurani, Tri Wiji; Mustaruddin, Mustaruddin; Herdiyeni, Yeni (Jurnal Teknologi Perikanan dan Kelautan, 2022)
The fishing season and abundance of pelagic fish were influenced by the dynamics of chlorophyll-a and sea surface temperature values. Information on fishing seasons and their relationship to oceanographic parameters could assist fishermen in increasing fishing efficiency. Therefore, this study aimed to determine the pelagic fishing seasons in Palabuhanratu waters and identified the dynamics of chlorophyll-a and sea surface temperature and their relationship to fishing seasons. The data used were pelagic production at 2016-2020, chlorophyll-a, and sea surface temperature values. The data were analyzed using the moving average method and pearson-correlation. The results of this study indicated that the fishing season for skipjack, tuna mackerel, mackerel, and sailfish generally occurred in the east season. There was a close relationship between the production of skipjack and tuna mackerel on monthly fluctuations in sea surface temperature and chlorophyll-a values (p-value < 0.05). An increase in the concentration of chlorophyll-a, and a decrease of sea surface temperature values would be followed by an increase in the production of skipjack and tuna mackerel in Palabuhanratu waters. The correlation index of skipjack to chlorophyll-a was in the strong category (r = 0.697), while that of tuna mackerel was in the medium category (r = 0.485). The correlation index of skipjack and tuna mackerel to sea surface temperature was in the medium category (0.40 < r < 0.599).